A versatile kinase mobility shift assay (KiMSA) for PKA analysis and cyclic AMP detection in sperm physiology (and beyond) - Novero, Analia G.; Curcio, Catalina; Steeman, Tomás J.; Binolfi, Andres; Krapf, Diego; Buffone, Mariano G.; Krapf, Dario; Stival, Cintia (Frontiers in Cell and Developmental Biology, 2024)
The cAMP-dependent protein kinase (PKA) is one of the most extensively distributed kinases among intracellular signal cascades, with a pivotal role in the regulation of various processes, including the capacitation of sperm cells. Traditional assessments of PKA activity relies on the utilization of [γ-32 P] ATP and the Kemptide substrate. This methodology presents several major drawbacks, including highcosts and health risks derived from the manipulation of radioactive isotopes. In this work we introduce an enhanced non-radioactive assay for quantifying PKA activity, termed KiMSA which relies on the use of a fluorescent-labeled Kemptide (Kemptide-FITC). Once the kinase reaction is terminated, the products can be easily resolved through electrophoresis on an agarose gel and quantified by fluorescence densitometry. We show that the KiMSA assay is suitable for purified PKA, and also to address both basal and capacitation induced PKA activity in mouse sperm cells. Furthermore, the assay enables monitoring the inhibition of PKA with inhibitors such as sPKI and H-89 in live cells. Therefore, the experimental and optimal assay conditions are set so that the KiMSA assay can be used to either assess in vitro as well as in vivo PKA activity in sperm cells. Finally, this method allows for measurement of cAMP concentrations, rendering a versatile technique for the study of cAMP/PKA pathways.